KEBERTAHANAN KOSAKATA KELADANGAN BAHASA JAWA DI DAERAH TRANSMIGRASI DESA WONUA RAYA KECAMATAN TOARI KABUPATEN KOLAKA - Fadhilah Febrianti; La Yani Konisi; Sulfiah (PT. CASA CENDEKIA MEDIA, 2025)
The problem of this research is how is the level of resilience of Javanese language field vocabulary in the transmigration area of Wonua Raya Village, Toari District, Kolaka Regency. The purpose of this study is to describe the resilience of Javanese language field vocabulary in Wonua Raya Village, Toari District, Kolaka Regency. The type of research used is field research using qualitative analysis methods and supported by quantitative analysis. Data collection techniques using questionnaires and interviews. The results of the study showed that from 80 vocabularies submitted to 50 respondents, namely respondents of late adolescence (17-25) years and early adulthood (26-35) years regarding the resilience of Javanese language field vocabulary in Wonua Raya Village, Toari District, Kolaka Regency, data was obtained on the total number of vocabularies still known by respondents as many as 3,518 vocabularies with a percentage of 87.95% while the total number of unknown vocabularies was 482 vocabularies with a percentage of 12.05%. With this percentage, the Javanese vocabulary in the transmigration area of Wonua Raya Village, Toari District, Kolaka Regency is still considered to be resilient.